Comportamiento dinámico de muros de mampostería no estructural reforzados mediante polímeros reforzados con fibra de carbono, CFRP (2015)
In many countries, buildings are made with unreinforced clay masonry walls, producing constructions with low resistance and ductility, very vulnerable to seismic events. This has been observed in previous earthquakes experiences, where the buildings behavior with non- structural walls was inadequate due to their low ductility and their low capacity of dissipation of energy, producing within them big failures that even made them collapse. Investigations have revealed that the use of reinforced polymers with carbon fiber (CFRP) bonded to masonry walls can increase the walls capacity of dissipation of energy, turning them into more resistant walls to lateral loads. This document reports the results obtained from a research where the behavior of nonstructural masonry walls regarding lateral loads when reinforced CFRP considering different anchoring systems to the foundation was evaluated. In the test program 14 clay masonry walls were built at a normal scale, using brick No. 5, which is the one normally used in this type of buildings. From the 14 walls, half of them were 1,23 meters long by 1,90 meters high and the other half of 2,47 meters long and 1,90 meters high. Eight walls were tested with static lateral load and six were reinforced and tested with cyclical lateral load in its plane. The answers of the walls were compared regarding the hysteretic behavior, maximum load, ductility and stiffness degradation. The results revealed that the reinforcement material significantly increased the ultimate load capacity, the sudden failure decreased because they were progressive and less fragile, attaining better performance levels of these elements.